2017
DOI: 10.15204/jkobgy.2017.30.1.042
|View full text |Cite
|
Sign up to set email alerts
|

Trends Analysis of Clinical Studies on Korean Medicine for Infertility

Abstract: Objectives: This study were investigated clinical studies published in international and Korea ' s journals to assess the effect of Korean Medicine for infertility.Methods: PubMed and Oriental Medicine Advanced Searching Integrated System (OASIS) were searched for this review up to Nov 2016.: using terms of ' infertility ' and ' subfertile ' .Results: Fifty clinical studies were finally selected. All studies were assessed as the noncomparative studies, and mainly case reports. The year of publication of litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, very few studies have been conducted to collect evidence of KM treatment effects on unexplained infertility. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very few studies have been conducted to collect evidence of KM treatment effects on unexplained infertility. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical trials have tested only the clinical efficacy and safety of single treatments and have ignored the complexities of KM interventions. 9 A recent multicenter observational study tested the effects of herbal medicines with acupuncture in women with unexplained infertility. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 5 In most cases, a combination of KM and conventional treatments were recommended. 6 Several studies reported that complementary treatments increase the success rate of the In Vitro Fertilization(IVF) treatment, 7 , 8 and Korean medicine by itself provided before IVF increases the likelihood of a successful natural pregnancy, while it also relieves menstrual cramping and increases hematological parameter stability of patients. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%